Revisi dan Implementasi Panduan Rotasi Klinik (Logbook)-Studi Kasus dalam Pendidikan Klinik di FK Universitas Mataram - Yoga Pamungkas; Sari, Dian Puspita (Faculty of Medicine Universitas Mataram, 2019)
Background: Clinical rotation guidance (logbook) in clinical education is very important to provide the structure and focus of teaching and learning activities for both students and clinical supervisors. Implementation of clinical education itself faces many challenges, however the problems and challenges in each faculty of medicine are different. This paper aims to identify the problems and challenges encountered during the revision process and the implementation of the logbook. Method: Case studies are carried out by taking notes during the curriculum revision and implementation process. The analysis was carried out by reflecting on the ongoing revision process. Results: Before the revision process, 10 of the 13 sections of the clinic had guidelines. The main problem faced is the lack of uniformity of perception about clinical rotation logbook and their contents. The revision process begins with socialization to build mutual commitment. The leadership of FK UNRAM has made an important contribution to building commitment and providing support for the revision process led by the Medical Education Unit (MEU). Through internal consolidation MEU developed the logbook format to be used. Prior to implementation, socialization to clinical supervisors and students was conducted to ensure smooth implementation. Conclusion: The revision of the clinical rotation logbook is basically changing the clinical education system and curriculum. Joint commitment of the clinical department, involvement and support of the leadership, active involvement of the clinician in decision making, as well as socialization of guidelines to all parties involved will support the success of this process.